Calculations of gaseous and particulate emissions from German agriculture 1990 - 2020: Report on methods and data (RMD) Submission 2022; Berechnung von gas- und partikelförmigen Emissionen aus der deutschen Landwirtschaft 1990 - 2020: Report zu Methoden und Daten (RMD) Berichterstattung 2022 - Cora Vos; Claus Rösemann; Hans-Dieter Haenel; Ulrich Dämmgen; Ulrike Döring; Sebastian Wulf; Brigitte Eurich-Menden; Annette Freibauer; Helmut Döhler; Carsten Schreiner; Bernhard Osterburg; Roland Fuß (Johann-Heinrich-von-Thünen-Institut, 2022)
The report at hand (including a comprehensive annex of data) serves as additional document to the National Inventory Report (NIR) on the German green house gas emissions and the Informative Inventory Report (IIR) on the German emissions of air pollutants (especially ammonia). The report documents the calculation methods used in the German agricultural inventory model Py-GAS-EM as well as input data, emission results and uncertainties of the emission reporting submission 2022 for the years 1990 - 2020. In this context the sector Agriculture comprises the emissions from animal husbandry, the use of agricultural soils and anaerobic digestion of energy crops. As required by the guidelines, emissions from activities preceding agriculture, from the use of energy and from land use change are reported elsewhere in the national inventories. The calculation methods are based in principle on the international guidelines for emission reporting and have been continuingly improved during the past years by the Thünen Institute working group on agricultural emission inventories, partly in cooperation with KTBL. In particular, these improvements concern the calculation of energy requirements, feeding and the N balance of the most important animal categories. In addition, technical measures such as air scrubbing (mitigation of ammonia emissions) and digestion of animal manures (mitigation of emissions of methane and laughing gas) have been taken into account. For the calculation of emissions from anaerobic digestion of animal manures and energy crops (including spreading of the digestate), the aforementioned working group developed, in cooperation with KTBL, a national methodology. [...] – – Der vorliegende Berichtsband einschließlich des umfangreichen Datenanhangs dient als Begleitdokument zum National Inventory Report (NIR) über die deutschen Treibhausgas-Emissionen sowie zum Informative Inventory Report (IIR) über die deutschen Schadstoffemissionen (insbesondere Ammoniak). Der Bericht dokumentiert die im deutschen landwirtschaftlichem Inventarmodell Py-GAS-EM integrierten Berechnungsverfahren sowie die Eingangsdaten, Emissionsergebnisse und Unsicherheiten der Berichterstattung 2022 für die Jahre 1990 bis 2020. Der Bereich Landwirtschaft umfasst dabei die Emissionen aus der Tierhaltung und der Nutzung landwirtschaftlicher Böden sowie aus der Vergärung von Energiepflanzen. Emissionen aus dem Vorleistungsbereich, aus der Nutzung von Energie sowie Landnutzungsänderungen werden den Regelwerken entsprechend an anderer Stelle in den nationalen Inventaren berichtet. Die Berechnungsverfahren beruhen in erster Linie auf den internationalen Regelwerken zur Emissionsberichterstattung und wurden durch die Arbeitsgruppe 'Landwirtschaftliche Emissionsinventare' des Thünen-Instituts in den vergangenen Jahren beständig weiterentwickelt, teilweise in Zusammenarbeit mit dem KTBL. Dies betrifft im Wesentlichen die Berechnung des Energiebedarfs, der Fütterung und der tierischen N-Bilanz bei den wichtigen Tierkategorien. Zusätzlich wurden technische Maßnahmen wie Abluftreinigung (Minderung von Ammoniakemissionen) und die Vergärung von Wirtschaftsdünger (Minderung von Methan- und Lachgasemissionen) berücksichtigt. Für die Berechnung von Emissionen aus der Vergärung von Wirtschaftsdünger und Energiepflanzen (einschließlich Gärrestausbringung) entwickelte die vorgenannte Arbeitsgruppe in Zusammenarbeit mit dem KTBL eine deutsche Methodik. [...]
urn:nbn:de:gbv:253-202203-dn064675-2
Keywords: 630; emission inventory; agriculture; livestock husbandry; agricultural soils; anaerobic digestion; energy crops; renewable primary products; greenhouse gases; air pollutants; methane; laughing gas; ammonia; particulate matter; Emissionsinventar; Landwirtschaft; Tierhaltung; landwirtschaftliche Böden; anaerobe Vergärung; Energiepflanzen; nachwachsende Rohstoffe; Treibhausgase; Luftschadstoffe; Methan; Lachgas; Ammoniak; luftgetragene Partikel; Staub